2010
DOI: 10.1007/s11695-010-0202-3
|View full text |Cite
|
Sign up to set email alerts
|

Excess Weight Loss Variation in Late Postoperative Period of Gastric Bypass

Abstract: Weight regain did not compromise therapeutic success. Less weight regain was seen in younger patients. Patients with lower intolerance to red meat tended to show less weight regain. Further studies are needed to elucidate the role of protein intake in weight regain in patients submitted to gastric bypass. No association between weight regain and preoperative BMI or gender was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 17 publications
2
14
0
3
Order By: Relevance
“…Weight regain usually starts at 24 months after surgery and is similar at 2, 5, 6 and 10 years after surgery, varying between 7% and 8.7% (2,12,13,16). Lowest values are demonstrated 3 years after surgery, showing 3% proportional weight regain (17).…”
Section: Discussionmentioning
confidence: 99%
“…Weight regain usually starts at 24 months after surgery and is similar at 2, 5, 6 and 10 years after surgery, varying between 7% and 8.7% (2,12,13,16). Lowest values are demonstrated 3 years after surgery, showing 3% proportional weight regain (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that some patients experience weight regain after RYGB . It is not uncommon for 20‐25% of initial weight loss to be regained by 10 years postoperatively .…”
Section: Discussionmentioning
confidence: 99%
“…Weight regain and surgical weight-loss "failure" have been reported to occur in a subset of patients 5-10 years after RYGB (9)(10)(11)(12)(13). It is unknown if weight regain is detrimental to the substantial metabolic improvements that occur after RYGB.…”
Section: Introductionmentioning
confidence: 99%
“…In general however, approximately 20 % of patients who undergo RYGB will experience weight regain over the 24 months after surgery. A variety of factors have been invoked to explain this phenomenon, including overeating, inappropriate diet, sedentarism and lack of regular exercise, metabolic factors, hormonal changes, inappropriate choice of surgical technique, gastrogastric fistulas, loss of function of the restrictive band when present, dilation of the gastric pouch, and dilation of the gastrojejunal anastomosis [2].…”
Section: Introductionmentioning
confidence: 99%